PERBEDAAN STUNTING BERDASARKAN PENGETAHUAN GIZI IBU DAN ASUPAN ZAT GIZI BALITA DI KECAMATAN UBUD - Ni Kadek Sintia Astari; Ni Made Yuni Gumala; Lely Cintari (Poltekkes Kemenkes Denpasar dan DPD PERSAGI Bali, 2019)
The stunting prevalence in Ubud Subdistrict is 28.6% where Ubud is a world tourist destination in Bali, but there are still stunting occurrences in the region. The study aimed to determine the differences in the incidence of stunting based on knowledge of maternal nutrition and nutrient intake in infants in the District of Ubud. The type and design of the study were observational with a cross sectional study design. The total population is 3766 toddlers with 50 samples. Stunting data was taken by measuring the height / length of the body, knowledge obtained by means of interviews using questionnaires and intake of toddlers obtained by doing 2x24 hour recall. A total of 36.0% experienced stunting while 64.0% did not stunting. The average knowledge of maternal nutrition is 60.12%. The average energy intake of toddlers is 1066.08 kcal, protein 26.36 gr and calcium 583.48 mg. The results of the analysis showed that there were differences in the incidence of stunting based on maternal nutrition knowledge (p = 0,000), there were differences in the incidence of stunting based on energy intake (p = 0,002), there were differences in the incidence of stunting based on protein intake (p = 0,015) and differences in intake of stunting calcium (p = 0.026).Key Words: stunting, knowledge, nutrient intake